Development of Learning Media Using the Powtoon Application for Effective Communication Courses in Diploma 3 Medical Record and Health Information Department - Zefan Adiputra Golo; Elise Garmelia; Asharul Fahyudi (Jurnal Penelitian Pendidikan IPA, 2022)
Communication between health workers and patients is still a major problem in health services. Learning media is needed that can be used by students of medical records and health information to improve effective communication. The purpose of this research is to develop effective communication learning video media using the Powtoon application. This research method uses the ADDIE product development model. Validation of the development of learning video media through learning media expert tests and expert tests for Effective Communication subject matter. Test the effectiveness of learning media through pre-test and post-test on 70 students. The results of the learning media expert test from 4 learning videos averaged 95.42% (very feasible) and the lecture material test from Effective Communication course lecturers averaged 95.90 (very feasible). The results of the analysis of the pre-test average value of 78 and the post-test average value of 92.71. Through Paired t-test: Result = 0.000. Meaning: There is a difference between before and after treatment (learning using videos). Reason: The p-value < 0.05 (95% confidence).